SMART CURRICULUM IMPLEMENTATION FOR SUSTAINABLE EDUCATION DEVELOPMENT IN NIGERIA - Ugwunnamchi , Uchenna Jacinta (Multi-Disciplinary Research and Development Journals Int’l, 2025)
The paper looked smart curriculum implementation for sustainable education development in Nigeria. Secondary data were used in the study. The data were collected from both print and online publications. Content analysis was used to analyze the selection of literature for the study. The paper concluded that smart curriculum implementation enhances personalized and adaptive learning digital skills and 21st-century competencies, improves teaching effectiveness, promotes collaborative and interactive learning enhances access, flexibility, and inclusiveness. The paper also revealed that inadequate ICT infrastructure, poor internet connectivity and high data costs, low digital literacy among teachers, high cost of technology acquisition and maintenance, resistance to change from teachers and administrators, lack of relevant and localized digital content and weak policy implementation and poor governance are some of the challenges hindering smart curriculum implementation in the Schools in Nigeria. Based on the findings, the paper recommends that government and stakeholders should prioritize investment in ICT infrastructure, including computers, smart boards, stable electricity supply, and secure school networks. Public–private partnerships (PPPs) can help expand digital facilities, especially in rural and underserved areas. The government should collaborate with telecommunication companies to provide schools with subsidized broadband services. Community-based internet hubs, solar-powered routers, and low-cost data plans should be introduced to ensure sustainable connectivity. T Government at all levels should allocate dedicated funds for digital education. Schools should adopt cost-effective solutions—such as open-source platforms—and create maintenance plans for repairing and upgrading ICT equipment.